EFFECT OF THE ADDITION OF MICROORGANISMS IN THE TREATMENT LIQUID EFFLUENT FISH MEAL INDUSTRY - Pizarro, Raúl (2007)
The study consists of the treatment of the pumping water of fish flour industry. The addition oí microorganisms in presence of ferric sulphate is managed to destabilize the system, obtainig that a watery solution "drains" towards the inferior part, floating solid free water particles. This behavior probably is due to the destruction of the substances that are in the different interphases when they are consumed by the microorganisms. The ferric sulfato, besides to give average acid for the reproduction of the microorganisms also contributes positive charges to the system which interacts with the acuatic system.